2003
DOI: 10.1152/ajpgi.00280.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-HT1B/D receptors in canine gastric accommodation: effect of sumatriptan and 5-HT1B/D receptor antagonists

Abstract: The 5-HT1B/D receptor agonist sumatriptan has been proposed to treat dyspeptic symptoms, because it facilitates gastric accommodation. It is unknown whether stimulation of 5-HT1B/D receptors is involved. Thus, in four conscious dogs, we compared the effects of sumatriptan alone or combined with N-[4-methoxy-3-(4-methyl-1-piperazinyl) phenyl]-2'-methyl-4'-(5-methyl-1,2,4-oxadiazol-3-yl)-[1,1-biphenyl]-4-carboxamide hydrocloride (GR-127935), N-[3-[3 (dimethylamino)-ethoxy]-4-methoxyphenyl]-2'-[methyl-4'-(5-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…30,31) It appears that stimulation of the 5-HT 1B receptor has a relaxation effect on gastric tone in dogs since the antimigraine 5-HT 1B/D receptor agonist sumatriptan induces an immediate gastric relaxation and gastric accommodation mediated by 5-HT 1B receptors. 19) The gastric barostat technique is the most common method for measuring gastric compliance and accommodation in both humans and animals. Corydaline induced gastric accommodation at a dose of 1 mg/kg but had no measurable effect on gastric tone.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…30,31) It appears that stimulation of the 5-HT 1B receptor has a relaxation effect on gastric tone in dogs since the antimigraine 5-HT 1B/D receptor agonist sumatriptan induces an immediate gastric relaxation and gastric accommodation mediated by 5-HT 1B receptors. 19) The gastric barostat technique is the most common method for measuring gastric compliance and accommodation in both humans and animals. Corydaline induced gastric accommodation at a dose of 1 mg/kg but had no measurable effect on gastric tone.…”
Section: )mentioning
confidence: 99%
“…19) Five female Beagle dogs (7-9 kg) were operated on under general anesthesia with Tiletamine/Zolazepam (Zoletil ® , Virbac Laboratories, Carros, France; i.v., 10 mg/kg). A chronic gastric fistula was inserted via a midline laparotomy in the larger curvature of the stomach between the glandular portion and forestomach and was exteriorized through the anterior aspect of the abdomen.…”
mentioning
confidence: 99%
“…1,2) The stimulation of 5-HT 1B/1D receptors induces gastric accommodation in humans 3) and dogs, 4) and delays gastric emptying in humans. 5,6) The blockade of 5-HT 3 receptors inhibits gastrointestinal motility in humans.…”
mentioning
confidence: 99%
“…The antimigraine drug sumatriptan, which has affinity at different 5-HT 1 -receptor subtypes, was shown to induce feline and human gastric fundus relaxation (27), indicating therapeutic potential in the treatment of patients with functional dyspepsia (FD) (6,26). In dogs, studied with a barostat, sumatriptan shifted gastric pressure-volume curves toward higher volumes and enhanced gastric accommodation, an effect mediated by 5-HT 1B receptors (8). Recently, we showed that flesinoxan induces proximal gastric relaxation in conscious dogs via 5-HT 1A receptors.…”
mentioning
confidence: 99%